Pattern of Injuries Sustained in Cases of Four Wheelers without wearing Seat Belt Infatal Road Traffic Accidents in Mangalore - Azia Manzoor Bhat; Wasim Manzoor Bhat; Vinka Maini (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Road traffic accidents (RTAs) have been the bane of the modern civilization accounting for considerableloss to the nation. General callous attitude for safety measures, poor law enforcement and uncontrolled motorizationhave caused significant increase in incidence of RTAs. World Health Organization (WHO) puts RTAs as the sixthleading cause of deaths in India, with a greater share of hospitalizations, deaths, disabilities and socioeconomic lossesin young and middle aged population.Aims and Objective: To study the pattern of injuries sustained in cases of four wheelers without wearing seat beltin fatal road traffic accidents in Mangalore.Materials and Method: All cases of road traffic accidents involving fatal head injuries among four wheelers withoutseat belt which underwent autopsy at the Wenlock District Hospital and Justice K.S Hegde charitable Hospital,Mangalore from January 2009 to December 2013 were included in the study. A proforma was prepared, the detailsabout the pattern of skull fractures and also about intracranial haemorrhages were obtained.Results:Majority of the victims of four wheeler not using seat belt were in the age group of 30-39 Years and 40-49Years (26.83% each). Majority of the victims were male (85.37%).Abrasion (46.34%) was the most common Injuryto face and head followed by laceration (29.27%) was observed.Rib fractures was the most common associatedinjury (43.90%) while no associated injury was observed in 56.10%.Diffuse Extravasation of Blood from Scalp wasobserved in 53.66% while from occipital are was seen in 26.83% victims. Linear Type of fracture in vault was seenin 36.59% of victims. Occipital and frontal bone fracture was observed in 29.27% and 24.39% victims respectively.While studying the Base of skull fractures it was seen that ACF was seen in 24.39% victims while PCF in 19.51%and MCF in 14.63% victims. Most common intra cranial haemorrhage was Sub arachnoid haemorrhage (90.24%)followed by sub dural haemorrhage (82.93%). Brain Oedema was seen in 73.17% victims while Contusion to brainwas seen in 26.83% victims. Frontal lobe of brain was injured in 46.34% victims while diffuse brain injury was seenin 29.27% victims.Conclusion:We conclude that the four wheeler accident among the non seat belt users was common in middle agedmales. Head injury and rib fracture was the most common type of injury observed. Liner fracture of skull withoccipital and frontal bone involvement was common. Most common intra cranial haemorrhage was Sub arachnoidhaemorrhage followed by sub dural haemorrhage. Brain Oedema and Contusion to brain were common brain injury.Frontal lobe brain injuries were common followed by diffuse brain injury.